Women’s economic roles in Islam: principles and perspectives - Kamaruddin, Zuraidah; Al Fijawi, Mohamed Farid Ali; Mustapha, Ariyanti; Che Haron, Sueraya (RSIS International, 2025)
This study examines the economic roles of women in Islam by analysing religious principles, historical accounts, and ethical guidelines that shape women’s contribution to economic life. Employing a qualitative approach, this study aims to analyse women’s economic roles from an Islamic perspective and to understand how Islamic teachings establish a framework for women’s participation in economic activities while upholding religious values. The findings demonstrate that Islamic teachings provide a balanced and comprehensive framework that recognises women’s capacity to contribute to economic development while preserving ethical and social order. Women’s economic roles in Islam are supported by both religious principles and historical precedent, reflecting a holistic worldview that integrates economic activities with moral and spiritual values. The study also reveals that women possess the right to pursue various economic activities according to their natural disposition, circumstances, capabilities, and interests, as long as these activities conform to Islamic guidelines. Furthermore, Islam offers a comprehensive set of ethical principles through Shariah to regulate human behaviour, including conduct within the economic domain. Overall, the study highlights that Islam affirms women’s roles within economic life in a manner that upholds dignity, ethical responsibility, and social stability, demonstrating the religion’s cohesive and principled approach to women’s contributions within society.